2016
DOI: 10.1080/01436597.2016.1191345
|View full text |Cite
|
Sign up to set email alerts
|

The past in the present: time and narrative of Balkan wars in media industry and international politics

Abstract: In this article, we explore various forms of travel writing, media reporting, diplomatic record, policy-making, truth claims and expert accounts in which different narrative perspectives on the Balkan wars, both old (1912-1913) and new (1991-1999), have been most evident. We argue that the ways in which these perspectives are rooted in different temporalities and historicisations and have resulted in the construction of commonplace and time-worn representations. In practical terms, we take issue with several p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The media represent current events to diverse audiences (Abazi & Doja, 2017) and influence popular perceptions of tourist destinations (Volcic et al, 2014). Accordingly, the media has become an important source of information for tourism researchers (Li et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The media represent current events to diverse audiences (Abazi & Doja, 2017) and influence popular perceptions of tourist destinations (Volcic et al, 2014). Accordingly, the media has become an important source of information for tourism researchers (Li et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, whichever reference to blood mentality in relation to postcommunist turbulence in Albania, or to sexual violence in former Yugoslavia, becomes fundamentally a pure rhetoric. Nevertheless, as argued elsewhere, similar interpretations contributed to construct the Balkan image of Southeastern Europe in international representations with decisive implications in the global politics of regional affairs, including the advocating of the policy of non-intervention in Bosnia and the further containment of Western Balkans [45][46][47]. As a result, the insistence on international security contributed to install a fundamental political and ethical distance between the West and the so-called Balkan wars.…”
Section: War Rapes In Former Yugoslaviamentioning
confidence: 76%
“…Rape may be analyzed by its effects on male group dynamics, military rankings, state and ethnic formations, forms of political recruitment, family reorganization, gender relations, economic and rural/urban differentiation, and forms of political recruitment and religious purity/pollution. Conflict-related rape and gender-based 2 Structural methodology is implicit in previous works on social morphology [32,33], processes of identity construction and cultural socialization [34,35], women's agency [36], the myth of many children within the so-called Albanian patriarchal extended family [1], the religious movements during much of Southeast European history and politics [37][38][39][40][41][42][43][44], the narrative legacies and international representations of Balkan wars and their implications in regional and international politics [45][46][47], or the transformations of European identity [48].…”
Section: War Rapes In Former Yugoslaviamentioning
confidence: 99%
“…There are many types of knowledge produced about the Balkan wars of 1912-1913 and the Yugoslav conflicts in the 1990s that focus in particular on nationalism and the statebuilding process in Southeast Europe as well as on the international representation of Southeast Europe. Already, a number of efforts in the growing field of critical Southeast European studies, which we examine in more detail elsewhere (Abazi and Doja 2016b, 2017, 2018, have convincingly demonstrated that the stereotypes and prejudices drawn on to construct the Balkan image of Southeast Europe in hegemonic international representations unabatedly fly in the face of ample empirical evidence. Such studies have conclusively challenged the essentialist claims of ruthless violence, war atrocities, aggressive nationalism and dirty politics of the Balkan wars, or the "inhumanity" of Southeast European peoples, during both the 1910s and the 1990s (Campbell 1998).…”
Section: Introductionmentioning
confidence: 92%